A correlational study of school counselor rapport and student connection to school - Brown, Lyndsey Ann (Kansas State University, 2021)
It has long been known that rapport between the client and the counselor is a predictor of counseling success. In the scope of work for school counselor meeting the needs of all students, school counselors work to build rapport and positive relationships with students. The need for further study was indicated to determine the extent to which a student having a strong counseling rapport with a school counselor positively impacts perceptions of his/her own connectedness to school and sense of the school climate. This correlational study seeks to explain the correlation between counselor rapport and school connectedness and counselor rapport and school climate. The results of the study indicate having rapport with the school counselor correlates positively with a connection to the school and the sense of the school climate. The number of visits a student has with the school counselor increases the opportunity for stronger rapport and enhanced relationships resulting in positive social-emotional, academic, and career outcomes.
Keywords: School counseling; School connectedness; School climate; Rapport